Vertical TiO2 Nanorods as a Medium for Durable and High Efficiency Perovskite Solar Modules - Azhar, Fakharuddin; Rajan, Jose; Francesco, Di Giacomo; Alessandro, L. Palma; Fabio, Matteocci; Irfan, Ahmed; Stefano, Razza; Alessandra, D'Epifanio; Silvia, Licoccia; Jamil, Ismail; Aldo, Di Carlo; Thomas, M. Brown (American Chemical Society, 2015)
Perovskite solar cells employing CH3NH3PbI3-xClx active layers show power conversion efficiency (PCE) as high as 20% in single cells and 13% in large area modules. However, their operational stability has often been limited due to degradation of the CH3NH3PbI3-xClx active layer. Here, we report a perovskite solar module (PSM, best and av. PCE 10.5% and 8.1%), which employs solution grown TiO2 nanorods (NRs) as electron transport layer, that showed an increase in performance (~5%) even after shelf life investigation for 2500 h. A crucial issue on the module fabrication was the patterning of the TiO2 NRs, which was solved by interfacial engineering during the growth process and using an optimized laser pulse for patterning. A shelf life comparison with PSMs built on TiO2 nanoparticles (NP, best & av. PCE ~7.9% & 5.5%) of similar thickness and on compact TiO2 layer (CL, best & av. PCE 5.8% & 4.9%) shows, in contrast to that observed for NR PSMs, that PCE in NP and CL PSMs dropped by ~50 and ~90%, respectively. This is due to the fact that the CH3NH3PbI3-xClx active layer shows superior phase stability when incorporated in devices with TiO2 NR scaffolds.